Obesitas dan Kanker Payudara pada Wanita di 13 Provinsi Indonesia (Analisis Data IFLS 5) - Eka Hardianti Arafah; Nuning Maria Kiptiyah (Politeknik Kesehatan Kemenkes Mamuju, 2020)
The prevalence of breast cancer in Indonesia in 2013 was 0.05% and is the second-highest prevalence of cancer after cervical cancer. One of the risk factors for breast cancer is obesity. The prevalence of obesity in women based on Riskesdas 2007 - 2013 has significantly increased (13.9%, 15.5%, and 32.9%). The research objective was to determine the relationship between obesity and the incidence of breast cancer in women in Indonesia. Based on the analysis of the Indonesian Family Life Survey (IFLS) 5 carried out in 2014, data on breast cancer, obesity, and other factors were obtained in 13 provinces. The study design was cross-sectional and used logistic regression data analysis. The analysis showed that the proportion of obese women suffering from breast cancer in 13 provinces in Indonesia was 0.3%. Logistic Regression Analysis showed that obese women had a protective effect of 0.5 times against breast cancer after being controlled by the age variable (POR = 0.4999; 95% CI 0.275 - 0.906). This study concluded that obesity was statistically related to a protective effect against breast cancer in women in 13 provinces in Indonesia in 2014 after being controlled by the age variable. However, the proportion of obesity and breast cancer in Indonesia tends to increase. Therefore, strict supervision of prevention programs for non-communicable diseases in Indonesia is required.